Hubungan Indeks Massa Tubuh (IMT) dengan Kadar Apolipoprotein B (ApoB) pada Remaja Overweight dan Obes - Danun, Neida Valeria; Kaligis, Stefana H.M.; Tiho, Murniati (e-Biomedik, 2016)
Abstract: Childhood obesity is one of the serious public health problems. Data from the World Health Organization in 2013 showed that about 42 million children were categorized as overweight and obese. Obesity is correlated with cardiovascular diseases. Apolipoprotein B is one of the solid predictors to diagnose cardiovascular disease in developing countries. This study aimed to determine the correlation between body mass index and Apolipoprotein B levels in overweight and obese adolescents. This was an analytical observational study with a cross sectional design. This study was participated by 23 overweight and obese adolescents. The results showed that the mean level of BMI in overweight and obese adolescents was 32 (SD±4.235) kg/m2, ApoB was 94,13 mg/dL (SD±19.770). The Spearman’s rank correlation test showed a significance level (P) = 0.587 and the correlations value (r) = 0,120 between body mass index and Apolipoprotein B levels. Conclusion: There was no significant correlation between BMI and ApoB in overweight and obese adolescents. Albeit, some of the overweight and obese adolescents have moderate risk to suffer from cardiovascular diseases in the future. Keywords: body mass index, apolipoprotein B, overweight, obese, adolescents Abstrak: Obesitas pada anak merupakan suatu masalah serius kesehatan masyarakat. Data dari Organisasi Kesehatan Dunia (WHO) tahun 2013 melaporkan sekitar 42 juta anak yang tergolong overweight dan obesitas. Obesitas memiliki hubungan erat dengan penyakit kardiovaskular. Apolipoprotein B merupakan salah satu prediktor kuat yang dipakai negara-negara maju untuk diagnosis penyakit kardiovaskular. Penelitian ini bertujuan untuk mengetahui hubungan indeks massa tubuh (IMT) dengan kadar Apolipoprotein B pada remaja overweight dan obes. Jenis penelitian ini analitik observasional dengan desain potong lintang terhadap 23 remaja overweight dan obes. Hasil penelitian mendapatkan nilai rata-rata indeks massa tubuh pada remaja overweight dan obes 32 (SD±4,253) kg/m2 dan nilai rata-rata kadar Apolipoprotein B pada remaja overweight dan obes 94,13 mg/dL (SD±19,770). Hasil uji korelasi Spearman mendapatkan nilai signifikan (P) = 0,587 dan korelasi (r) = 0,120 antara indeks massa tubuh dengan kadar Apolipoprotein B. Simpulan: Tidak terdapat hubungan antara indeks massa tubuh dengan kadar Apolipoprotein B pada remaja overweight dan obes. Walaupun demikian, sebagian remaja overweight dan obes memiliki risiko sedang terkena penyakit kardiovaskular di masa mendatang.Kata kunci: indeks massa tubuh, apolipoprotein B, remaja, overweight, obes